2019
DOI: 10.1016/j.ygyno.2018.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Stratified risk of high-grade cervical disease using onclarity HPV extended genotyping in women, ≥25 years of age, with NILM cytology

Abstract: This study utilized extended genotyping to stratify ≥CIN3 and ≥CIN2 risk in women, ≥25 years, with NILM cytology. • HPV 16 and 31 carried the highest risk for ≥CIN3 and ≥CIN2. • Individual genotype reporting revealed risk strata associated with genotype groupings for ≥CIN3 and ≥CIN2. • Clinical management for risk-based screening is discussed in the context of extended genotyping results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…In another study, however, Cuzick et al showed that HPV16 retains its high risk, while HPV31 and especially HPV33 emerge as important types with higher positive predictive values (PPVs) than HPV18 [19] . Thus, individual HPV genotypes within commonly grouped categories of "Other hrHPV types" do not carry equal risk, and separate assessment of HPV 33 and 31 needs to be reconsidered [19,20] . In this cohort, Other hrHPV infection was most prevalent, accounting for 79.9% of hrHPV infections, and contributed to substantial cytological abnormalities as well as large proportions of CIN2/CIN3 (62.7% and 43.9%, respectively) over 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, however, Cuzick et al showed that HPV16 retains its high risk, while HPV31 and especially HPV33 emerge as important types with higher positive predictive values (PPVs) than HPV18 [19] . Thus, individual HPV genotypes within commonly grouped categories of "Other hrHPV types" do not carry equal risk, and separate assessment of HPV 33 and 31 needs to be reconsidered [19,20] . In this cohort, Other hrHPV infection was most prevalent, accounting for 79.9% of hrHPV infections, and contributed to substantial cytological abnormalities as well as large proportions of CIN2/CIN3 (62.7% and 43.9%, respectively) over 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the current HPV assays may require a modification, such as adding more previously low prevalence hrHPV subtypes and separating each genotype [25] . Recently, a growing number of low-cost HPV tests have been developed to distinguish extended genotypes [20,26] , which makes the better understanding of individual types and the better evaluation of vaccine effects. In order to reduce the burden of cervical diseases, the bivalent vaccine (covering HPV16 and 18), quadrivalent vaccine (covering HPV 16,18,6 and 11) and nonvalent vaccine were licensed in China successively since 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence estimates were restricted to subjects with key demographic information, evaluable liquid-based cytology results, and valid HPV assay results for all genotypes. For risk determination, values were determined hierarchically using an order established previously by Stoler and colleagues [16]. In that report, a Bayesian model (derived by Markov-Chain Monte Carlo methods) was utilized to hierarchically rank the nine different genotype Onclarity channels based on ≥CIN3 baseline risk (for subjects with co-infections, the model assigned the ≥CIN3 risk as equal to the highest-risk genotype).…”
Section: Discussionmentioning
confidence: 99%
“…The design of the Onclarity HPV trial has been described previously in depth [8,15,16]. In brief, 33,858 subjects, ≥21 years, undergoing routine cervical cancer screening were recruited at 31 clinical sites in 17 states.…”
Section: Study Design and Enrollment Visitmentioning
confidence: 99%
“…It is not known how many more would have been diagnosed with random biopsy. A US trial reported an 8.5% prevalence of CIN3 in women with normal cytology referred to colposcopy and biopsy (directed or random) after a single positive test for HPV16/18 . Women with HPV infection and normal cytology form the majority of the triage population, and there is an urgent need for better evidence to inform colposcopy management guidelines for these women.…”
Section: Discussionmentioning
confidence: 99%